Memaknai Arsitektur dan Ragam Hias pada Rumah Khas Betawi di Jakarta sebagai Upaya Pelestarian Budaya Bangsa - Polniwati Salim (Bina Nusantara University, 2015)
Indonesia is an archipelago country with various ethnics which have specific culture. One of the most popular cultures is Betawi culture in which people grew and spreaded in a city used to be called as Batavia. Nowadays, the variety of Betawi culture can be obviously seen by language, art, dance, ceremony, tradisional clothes, architecture, and ornaments. In order to preserve the culture, discussing and analyzing Betawi tradisional house with its ornaments and architecture is very important. The architecture which shows symbols and ornaments in all over the design can be found at the ethnic house. Betawi ethnic house consists of many symbols that represent meaning of the art and delivers some messages for people. This study was carried with comparative analysis and descriptive method. Research results show all Betawi architectural and ornaments could bring benefits and support preservation. The preservation included protecting and developing, and at the same time, making use of it as the cultural inheritance that has high values.